1994
DOI: 10.1139/x94-092
|View full text |Cite
|
Sign up to set email alerts
|

Bark properties and fire resistance of selected tree species from the central hardwood region of North America

Abstract: Some physical, thermal, and chemical properties of bark of 16 tree species native to the central hardwood region were measured to determine their potential to protect the vascular cambium from damage by fire. The relationship between DBH and bark thickness for each of 16 species was determined. For purposes of monitoring seasonal trends, two species (Quercusmacrocarpa Michx. and Acersaccharinum L.) were sampled periodically during one growing season. Temperature response to bark surface heating of 11 species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 0 publications
4
133
1
Order By: Relevance
“…The estimated GWR model strongly suggested that the impacts of red pine trees on burn severity were not constant over space; rather, the effects varied among locations (i.e., non-stationary effects). The effect of red pine might not be the same across the entire study area; rather, it could vary among sites depending on complex environmental factors, meteorological conditions, and individual tree characteristics [19,31,[68][69][70]. However, the cause of this non-stationary effect of red pine trees on burn severity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated GWR model strongly suggested that the impacts of red pine trees on burn severity were not constant over space; rather, the effects varied among locations (i.e., non-stationary effects). The effect of red pine might not be the same across the entire study area; rather, it could vary among sites depending on complex environmental factors, meteorological conditions, and individual tree characteristics [19,31,[68][69][70]. However, the cause of this non-stationary effect of red pine trees on burn severity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Bark insulates the cambium from heat and is not easily combustible; therefore, thicker bark provides more protection. The rate of thickening differs by species, individual genetic differences, and environmental factors, and it influences how quickly this insulating layer forms (Hare 1965;Hengst and Dawson 1994). Species that develop thick bark early in life become fire-resistant sooner and are adapted to survive frequent, low-intensity fire.…”
Section: First Order Tree Responses To Heat Injurymentioning
confidence: 99%
“…The insulating quality of bark is also affected by its structure, composition, density, and moisture content (Hare 1965;Reifsnyder and others 1967), factors that vary among species. For example, among central hardwoods, bark of silver maple has a high specific gravity and thermal conductivity, and can transmit heat to cambial layers in less time than bark with a low specific gravity and conductivity, such as bur oak and eastern cottonwood (Hengst and Dawson 1994). Flame length (Brown and DeByle 1987), flaming residence time (Wade 1986), and stem char height (Regelbrugge and Conard 1993;Regelbrugge and Smith 1994) can be related to the amount of mortality of thinbarked trees.…”
Section: Stem Mortalitymentioning
confidence: 99%